Is Watching TV Series an Adaptive Coping Strategy During the COVID-19 Pandemic? Insights From an Italian Community Sample - Boursier, Valentina; Musetti, Alessandro; Gioia, Francesca; Flayelle, Maèva; Billieux, Joël; Schimmenti, Adriano (Frontiers in Psychiatry, 2021)
Social distancing and lockdown due to the COVID-19 pandemic substantially impacted individuals’ daily habits and well-being. Within such a context, digital technology may provide a welcome source of alternative forms of connection and entertainment. Indeed, streaming services showed a remarkable increase in membership subscriptions throughout the period considered. However, excessive involvement in watching TV series has recently become a subject of scholarly concern as it may represent an emerging form of addictive behavior with the features of what has been labelled as “binge-watching” (i.e., watching multiple episodes of TV series in a single session). The current study aimed to assess TV series watching behaviors and related motivations, as well as their relationships with depression, stress and anxiety, in a sample of Italian adults during the COVID-19 lockdown. Specifically, we aimed to explore which patterns of motivations and emotional states influenced either a high but healthy engagement in watching TV series, or promoted problematic and uncontrolled watching behavior under such circumstances. A total of 715 adults (M = 31.70, SD = 10.81; 71.5% female) from all over Italy were recruited (from 1st to 30th April 2020) through advertisements via social media platforms of Italian university communities and other online groups. Two multiple hierarchical regression analyses were performed with non-problematic and problematic TV series watching set as dependent variables. Results showed that people spent more time watching TV series during the pandemic lockdown, especially women who also reported higher levels of anxiety and stress than men. Moreover, both non-problematic (R2 = 0.56; p < 0.001) and problematic (R2 = 0.33; p < 0.001) TV series watching behaviors were equally induced by anxiety symptoms and escapism motivation, thereby evidencing that watching TV series during the COVID-19 lockdown probably served as a recovery strategy to face such a stressful situation. Finally, our findings also suggest that enrichment motives may protect from uncontrolled and potentially addictive watching behaviors. These findings, therefore, hold important implications, particularly for avoiding the over-pathologization of excessive involvement in online activities emerging as a result of specific distressing situations.